Amino-functionalized Zr-MOF nanoparticles for adsorption of CO2 and CH4 - Abid, H.; Shang, J.; Ang, Ha-Ming; Wang, Shaobin (Taylor and Francis, 2013)
Amino-functionalized Zr-MOF (amino-Zr-MOF) was synthesized using 2-aminoterephthalic acid as an organic linker. The physicochemical properties of the material were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and N2 adsorption to understand its crystalline structure, morphology, thermal stability, and porous structure. CO2 adsorption isotherms on amino-Zr-MOF were obtained at 1 atm and at different temperatures. In addition, CO2 and CH4 adsorption at high pressure (up to 10 atm) was also measured. CO2 adsorption capacity on amino-Zr-MOF was 9 mmol/g at 988 kPa, 0°C, while CH4 adsorption capacity was 3.7 mmol/g at 900 kPa, 0°C. The heat of CO2 adsorption on amino-Zr-MOF was estimated to be 29.4 kJ/mol. Continuous column tests of CO2 adsorption were performed at different concentrations of CO2 in nitrogen at 20 mL/min and 0.7 g adsorbent and total adsorbed amounts of CO2 within the column during the breakthrough time were calculated to be 4.55, 5.26 and 4.37 mmol/g at 10%, 15% and 20%CO2, respectively.